Triangular Fibrocartilage Complex Repair All Arthroscopic Knotless - Mollie Manley, MD, MS (Journal of Hand Surgery Global Online)
Triangular fibrocartilage complex repair is an evolving technique. There are techniques to repair the tissue back to capsule or bone. It has been considered the gold standard to repair foveal tears back to bone. This first started as a fully open procedure and evolved to an arthroscopic-assisted procedure with drill holes and tunnels in the ulna. With this current technique, the incisions do not have to be any larger than the arthroscopic port holes.